The Effect Of Reward System On Employee's Job Satisfaction Study In Singosari National Artificial Insemination Center - Widyastiara, Khairi; Silvianita, Anita (2020)
Human resources are important assets in the which can be a source of strength and competitive advantage for the company if it managed properly. Therefore, it is very important for companies to maintain the welfare of employees, because fluctuations in the quality of employees are inseparable from the influence of job satisfaction of the employees. Reward is one of the determinants of job satisfaction. This is a reward system for employees' job satisfaction of Singosari National Artificial Insemination Center. A quantitative causal method, this is a quantitative causal method. Through the results of the results of the simple linear regression process, the results of the study show that the reward system has a significant effect on employees' job satisfaction by 51.7% while the remaining 48.3% are other factors outside of this research. In the future, BBIB Singosari has to be more clear about employee salaries and overtime wages. Therefore, it will be proportional. This can be encouragement for employees to be able to work harder and so they can improve the performance achievments.